Pengaruh Stock Split Terhadap Harga Dan Likuiditas Saham - Zainal Abidin Zein; Novita Indrawati; Eka Hariyani (Fakultas Ekonomi dan Bisnis, Universitas Riau, 2009)
This study aimed to analyze the effect of stock split announcement to the stock priceand liquidity in the Indonesian Stock Exchange by taking a sample of 34 firms in theperiod 2002 to 2005. During the study period 111 days, divided into two periods,100 day estimation period and event period 11 days including five days before, oneday events, and five days after. To examine the changes in prices made during thetest period abnormal return events with analysis based on the concept of marketmodel. Observed stock liquidity through trading activities/Tranding Volume Activity(TVA). The testing device used is one sample t-test and paired sample t-test. Theresults show that there is a significant abnormal return on stock split, there aresignificant differences in abnormal return between the periods before and after thestock split, and there was no significant difference in the activity of stock tradingvolume between the period before and after the stock spli